THE INFLUENCE OF PRINCIPAL EXEMPLARY LEADERSHIP AND SUPERVISION ON EDUCATOR DISCIPLINE - Ishlahati Ishlahati; Suswati Hendriani; David David (Lingeduca: Journal of Language and Education Studies, 2026)
Teachers’ work discipline is a strategic aspect in supporting the effectiveness of educational implementation and the achievement of school organizational goals. However, empirical conditions in junior high schools across Kamang Baru District, Sijunjung Regency indicate that teachers’ work discipline remains suboptimal, as reflected in tardiness, low compliance with teaching schedules, and the less-than-optimal implementation of administrative duties. This study aims to analyze the influence of principals’ role modeling and supervision on teachers’ work discipline. The study employed a quantitative approach using an associative method through an explanatory research design. The sample consisted of 64 teachers selected through random sampling from a total population of 174 teachers. Research data were collected through questionnaires that had met validity and reliability criteria, and were analyzed using descriptive and inferential statistics through simple linear regression and multiple linear regression with the assistance of SPSS version 27. The findings reveal that principals’ role modeling has a significant effect on teachers’ work discipline, contributing 21.4% and categorized as moderately strong. Principals’ supervision also has a significant effect on teachers’ work discipline, contributing 18.1% and categorized as low. Simultaneously, principals’ role modeling and supervision have a significant effect on teachers’ work discipline with a total contribution of 25.1%. These findings confirm that the effectiveness of school leadership through strengthening role modeling and optimizing supervisory functions plays an important role in improving teachers’ work discipline as part of strengthening effective school governance.